(untitled) (Global Journal of Human-Social Science, 2020)
The objective of this article is to analyze the role of the quality of institutions on the resilience of extreme exchange rate regimes to currency crises. To do this, in order to reach our goal, we used a logit regression on the data of 134 IMF member countries during the period 1984-2013. The results of econometric estimates obtained with the logit model show that: using the IMF classification, we find that there is no significant link. But using the de facto one, we find that, the bipolar hypothesis is not verified because, fixed exchange rate regimes decrease the probability of crisis while floating exchange rate regimes increase it. So the resilience of fixed regimes to exchange rate crises is higher than that of floating regimes. However, the hypothesis that the resilience to currency crises of different bipolar regimes is positively influenced by institutional quality is also ver ified. Because, this resilience increases in both exchange rate regimes, with less involvement of the military and religion in politics and the strengthening of the rule of law.